Frontolimbic Activity and Cognitive Bias in Major Depression - Poulsen, Catherine (2009)
In order to explore neural activity that accompanies cognitive bias in mood disorders, clinically depressed and non-depressed controls completed a self-evaluation procedure in which they indicated whether trait words were self-descriptive or not. Dense array (256-channel) electroencephalography (EEG) was recorded. Greater depression and low Positive Affect were associated with decreased endorsement of favorable (Good) traits, and greater anxiety and high Negative Affect with increased endorsement of unfavorable (Bad) traits. For controls, the event related potential (ERP) showed an enhanced visual N1 for trials in which Bad traits were endorsed. For depressed participants, this N1 was attenuated, specifically for these endorsed-Bad trials. A similar pattern was observed in the medial frontal P2-MFN complex, with controls showing an enhanced medial-frontal negativity to the endorsed Bad words, while depressed participants showed an attenuated or absent medial-frontal response on these items specifically. Distributed linear-inverse source analysis of the ERP localized the N1 effect to inferotemporal-occipital cortex, and the medial-frontal effect to dorsal anterior cingulate cortex. The altered ERP responses in depressed participants may provide clues to the neurophysiological processes associated with negatively biased cognition and self-evaluation in clinical depression.